2008
DOI: 10.1126/science.1153651
|View full text |Cite
|
Sign up to set email alerts
|

The Right and the Good: Distributive Justice and Neural Encoding of Equity and Efficiency

Abstract: Movies S1 and S2 Correction (29 May 2008):The original SOM text incorrectly said that "each child gets $5." The correct text now states that "each set of 3 children was endowed by the experimenters with $5, the monetary equivalent of 24 meals per child."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

26
264
2
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 309 publications
(301 citation statements)
references
References 23 publications
26
264
2
1
Order By: Relevance
“…Connectivity analyses suggested that, during decision making, RTPJ communicates information about the worst possible outcome to the caudate, a region involved in computing choice values (7). These results are consistent with growing evidence that decision making for self and others involves shared neurocognitive mechanisms (8) and imply that alternative perspectives-those of others, or of future selves-are integrated into a common valuation circuitry during decision making.…”
supporting
confidence: 76%
“…Connectivity analyses suggested that, during decision making, RTPJ communicates information about the worst possible outcome to the caudate, a region involved in computing choice values (7). These results are consistent with growing evidence that decision making for self and others involves shared neurocognitive mechanisms (8) and imply that alternative perspectives-those of others, or of future selves-are integrated into a common valuation circuitry during decision making.…”
supporting
confidence: 76%
“…In experiments involving efficiency and inequity tradeoffs in a distributive justice task, Hsu et al (2007) found a separation of regions encoding efficiency and inequity in much the same way as that of expected reward and variance. Specifically, efficiency is encoded in striatal regions including the caudate and putamen, whereas inequity is encoded in the insular cortex.…”
Section: Valuation Under Pure Risk: Trading Off Risk Against Rewardmentioning
confidence: 99%
“…Valuation-related neural brain structures may also be implicated in abstract social decisions that do not involve any personal gains or losses for the participant. For instance, decisions about the distribution of money between different groups of African children elicited neural activity related to both equity (how fairly is the money split) and efficiency (how much money in total is given) 97 . Inequity correlated with BOLD activity in the insula, whereas efficiency correlated with BOLD activity in the striatum, suggesting separate neural coding of both of these putatively decision-relevant social principles in the brain's reward circuitry.…”
Section: Neural Valuation Of Normative Social Principlesmentioning
confidence: 99%